A qualitative study on factors for freshmen’s mobile phone addiction and its influence on their classroom learning - Antony Fute; Yifan Feng; Feifei Huang; Xiangdan Zhao; Daniel Kangwa; Mohamed Oubibi (Discover Education)
Abstract Students’ excessive reliance on mobile phones during English classes diminishes their learning engagement and understanding, which in turn affects their academic performance. Teachers’ prior observations at our selected university indicated that smartphone usage among English learners varied significantly across class groups and among individual students within groups. This study employed a mixed-tactics approach (i.e., interviews, classroom observations, and group discussions) to uncover influential factors (both environmental and psychological) shaping students’ behaviour of smartphone overuse during English learning hours. The key findings have underscored the impact of environmental variables, such as class size es that are un that are unmanageable) and examination policies (i.e., not having final exams at the end of the semester), alongside psychological factors like self-discipline (self-control) and motivation. Generally, this study highlights the need for targeted interventions (within the university) and enhanced classroom management strategies (by teachers) to alleviate or lessen digital distractions and bolster learning engagement. The study advocates for promoting digital wellness initiatives and collaborative efforts to support students’ English learning engagement while prioritizing well-being in educational contexts.